The Effect of Inpatient Service Quality at Anutapura Hospital on the Patients Satisfaction - Rizaldi, Muhammad Adzmil; Afni, Nur; Kadri, Abdul (Universitas Muhammadiyah Palu, 2021)
According to the Law of the Republic of Indonesia No. 44 of 2009, Hospital is a health service institution that organizes complete individual health services that provide inpatient and emergency services. This research aims to determine the effect of the inpatient services quality at Anutapura Hospital on patients satisfaction. This is quantitative research with a cross-sectional study design. The sampling was conducted by using the proportional method to 68 inpatients of Anutapura Hospital, Palu. The analysis technique uses simple linear regression analysis. The results of this research indicate that the variables that have a positive and insignificant effect on patient satisfaction are physical evidence variable with a coefficient value of 0,057 and a sig value of 0,731> 0,05, a reliability variable with a coefficient value of 0,216 and a sig value of 0,119> 0,05, responsiveness with a coefficient value of 0,295 and a sig value of 0,100> 0,05, a guarantee with a coefficient value of 0,279 and a sig value of 0,099> 0,05, and attention with a coefficient value of 0,404 and a sig value of 0,096> 0,05. This research suggests that the agency should be able to improve services in terms of room provision, service support equipment such as seats for the patient's family who visit and can consider the needs of the community who come for treatment.